New Private Infrastructure Activity in Developing Countries Recovered in the First Half of 2009 Thanks to the Electricity Sector, But the Crisis Continues to Impact Projects - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
New private activity in infrastructure continues to take place in developing countries despite the financial and economic crisis. New projects are being tendered and brought to financial or contractual closure. Measured by amount of investment, the rate of project closure grew by 2 percent in the first half of 2009 compared to the first half of 2008, indicating a strong recovery from the decline of 48 percent experienced in the second half of 2008. This recovery, however, was driven by large projects. Measured by number of projects reaching closure, the rate of project closure continues to be slower than before the full-scale onset of the financial crisis. The number of projects reaching closure in the first half of 2009 was 20 percent lower than the number reported in the first half of 2008. This trend suggests greater project selectivity. Indeed, those projects that are reaching closure are characterized by strong economic and financial fundamentals, the backing of financially solid sponsors and governments. Developing country governments' continuing commitment to their public-private partnership (PPP) programs is confirmed by the number of new projects tendered and awarded. However, current market conditions are forcing governments and investors to restructure projects to improve financial viability. Local public banks as well as bilateral and multilateral agencies continue to be active in project finance, providing a critical amount of funding. It is too early to assess the full impact of the crisis on new infrastructure projects with private participation (PPI). The crisis continues to make financing (both debt and equity) more difficult to secure, and hamper the ability of governments to maintain financial commitments to public-private infrastructure projects.